ADAPTASI KURIKULUM MERDEKA DALAM PENGEMBANGAN KOMPETENSI VOKASIONAL DI SMTK BENFOMENI KAPAN - Christiana, Marya Dorince; Murniarti, Erni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
The research focused on the strategies of schools and educators in linking the principles of the Independent Curriculum to improve students' vocational skills readiness in accordance with the context of religious schools. This research used a qualitative approach with a descriptive study approach, enabling researchers to gain a deep understanding of the phenomenon under study. The research subjects included the principal, teachers, and students of SMTK Benfomeni Kapan who were directly involved in the implementation of the Independent Curriculum. Data collection techniques were carried out through field observations and documentation studies. The results showed that the adaptation of the Independent Curriculum at SMTK Benfomeni Kapan was realized through the implementation of differentiated learning, project-based learning, and the strengthening of the Pancasila Student Profile Strengthening Project (P5) integrated with religious values. These strategies contributed positively to the development of students' vocational competencies, particularly in aspects of independence, cooperation, creativity, and practical skills relevant to the needs of life and service. However, this study also found obstacles in aspects of teacher pedagogical competency and learning management, especially related to diagnostic assessment and systematic vocational learning planning.